NATIONAL REHABILITATION THROUGH LABOUR: A CASE STUDY OF KOREAN KOLKHOZES IN THE UZBEKISTAN SSR (1937–1980) (The Conference Hub, 2025)
Between 1937 and 1938, over 172,000 ethnic Koreans were deported from the Soviet Far East to Central Asia under NKVD Resolution No. 1428–326ss, justified as a measure “to suppress Japanese espionage in the Far Eastern territories” [1, p.2]. However, historians such as Gelb (1995) emphasize that the deportation was part of Stalin’s broader ethnic engineering project rather than a genuine security concern [2, p.36–38]. The deported population included even remote communities from Okhotsk and Magadan, far beyond any military relevance [1, p.2; 2, p.40].